Application of the rules of equity in land law in Malaysia: the controversies, necessity and the extent of such application / Ahmad Zulfikri Ibrahim, Muhammad Aizuddin Hang Md Kashap and Syafiqah Nadia Kamal Baharin - Ibrahim, Ahmad Zulfikri; Hang Md Kashap, Muhammad Aizuddin; Kamal Baharin, Syafiqah Nadia (2011)
This research aims to identify the inconsistencies of the application of the rules of equity and trust in land matters. The research divides the analysis into three parts. Those parts in which are firstly, in regards to Jual Janji, Lien, and Charge, secondly, the position of the Law of Contract in these dealings, and the issues of application of doctrines of trust in dealing in land matters. Upon identification of the inconsistencies, the research also critically weighs the argument of each interpretation as to the extent of the application of the rules of equity and trust in land matters. This research had found that the applicability of the rules of equity and trust had received mixed reaction from the legal industry. This difference in approach had conjured much debate within members of the legal fraternity. Ultimately, the examination of the cases had unraveled injustices whether if the law is rigid or lenient to such application. This research then proposes amendments to the Civil Law Act and recommendations as to the Rule of Law to be followed in order to develop a system of law which can successfully and justly caters to the symbiosis of the Malaysian Land Law and the Common Law Principles of Equity and Trust.